Marriage by design : a novel Lynn Michaels.. - Michaels, Lynn. (Ivy Books contemporary romance., 2006)
The top designer at her father's bridal design company, Mia Savard faces a milestone in her life, after turning thirty and suddenly finding herself single again after being dumped, a situation that is complicated when her most recent design is leaked to the competition and P.I. Joe Kerr is called in to find the insider responsible.